The impact of dyslipidemia on lumbar intervertebral disc degeneration and vertebral endplate modic changes: a cross-sectional study of 1035 citizens in China - Liang Yuan; Zhengqi Huang; Weitao Han; Ruiming Chang; Bo Sun; Mingxi Zhu; Chenjing Li; Jiansen Yan; Bin Liu; Haidong Yin; Wei Ye (BMC, 2023)
Abstract Background Intervertebral disc degeneration (IDD) and vertebral endplate Modic changes (MCs) are common lumbar degenerative phenotypes related to low back pain (LBP). Dyslipidemia has been linked to LBP but its associations with IDD and MCs have not been fully elucidated. The present study aimed to address the possible link between dyslipidemia, IDD and MCs in the Chinese population. Methods 1035 citizens were enrolled in the study. The levels of serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG) were collected. IDD was evaluated based on the Pfirrmann grading system and subjects with an average grade ≥ 3 were defined as having degeneration. MCs were classified into typical types 1, 2 and 3. Covariables, including age, sex, BMI and fasting plasma glucose, were included for the adjustment of the logistic analyses. Results The degeneration group included 446 subjects while the nondegeneration group included 589 subjects. The degeneration group had significant higher levels of TC and LDL-C (p < 0.001) whereas TG and HDL-C were not significantly different between the two groups. TC and LDL-C concentrations were significantly positively correlated with average IDD grades (p < 0.001). Multivariate logistic regression revealed that high TC (≥ 6.2 mmol/L, adjusted OR = 1.775, 95% CI = 1.209-2.606) and high LDL-C (≥ 4.1 mmol/L, adjusted OR = 1.818, 95% CI = 1.123-2.943) were independent risk factors for IDD. Type 1 MC presented in 84 (8.12%) subjects, type 2 MC presented in 244 (23.57%) subjects, type 3 MC presented in 27 (2.61%) subjects and no MC was observed in the remaining 680 (65.70%) subjects. The type 2 MC group demonstrated a higher level of TC, but the association between serum lipids and MCs could not be confirmed in further multivariate logistic regression. Conclusions High TC (≥ 6.2 mmol/L) and LDL-C (≥ 4.1 mmol/L) concentrations were independent risk factors for IDD for citizens in China. However, the association between dyslipidemia and MCs could not be determined. The effect of excess serum cholesterol may be critical for IDD and cholesterol lowering treatment may provide new opportunities in the management of lumbar disc degeneration.